Thermal energy saving and physico-mechanical properties of foam concrete incorporating form-stabilized basalt powder/capric acid based composite phase change material - Kocyigit, Fatih; Bayram, Muhammed; Hekimoglu, Gokhan; Cay, Vedat Veli; Gençel, Osman; Ustaoğlu, Abid; Sari, Ahmet; Gençel, Osman; Ustaoğlu, Abid (Elsevier Sci Ltd, 2023)
The incorporation of phase change materials (PCM) in construction materials for the purpose of thermal energy storage (TES) can prevent temperature fluctuations and enable the conservation of thermal energy in buildings. Accordingly, this study aims to create a novel, environmentally friendly foam concrete incorporating a composite PCM composed of capric acid saturated waste basalt powder. Basalt powder, a byproduct of the grinding or crushing of basalt volcanic rock, was selected as a carrier material due to its high porosity resulting from its lightweight and porous nature. This allowed for the creation of a leak-free composite PCM, which was then integrated with foam concrete made of CEM I 42.5R cement, water, quartz sand, and a foaming agent. BasaltPCM was substituted into the mixture at 50% and 100% by weight of quartz aggregate. Comprehensive evaluations were conducted on the novel foam concretes with regard to their morphological, mechanical, physical, thermal, and TES properties. The results indicate that the incorporation of basalt-PCM causes a minor reduction in the dry unit weight of the mixtures and a reduction in compressive and flexural strength. However, the leakproof basalt powder/capric acid composite displayed a phase transition behavior, melting at 28.5 degrees C with a latent heat of fusion (47.9 J/g), which retained 99.5% capacity after 500 melting-solidification cycles. The specimen with 100 wt% basalt-PCM exhibited a melting temperature and latent heat of 27.8 degrees C and 17.4 J/g, respectively. Additionally, the basalt powder/capric composite exhibited high thermal stability up to 156 degrees C, far above its normal operating temperature. The foam concretes incorporating the basalt-PCM demonstrated solar thermoregulation properties, maintaining a more stable and comfortable indoor temperature. These results suggest that the form-stable PCM-incorporating foam concretes developed in this study can be considered as environmentally friendly building materials for thermoregulation and energy conservation.
Keywords: Capric Acid; Phase Change Material; Basalt Powder; Foam Concrete; Thermal Energy Storage